Search for a Theoretical Basis for UDC: A Post-Script to the Herceg-Novi Symposium - Neelameghan, A. (Journal of Information and Knowledge, 1971)
The main points of the papers presented and the concensus of the discussion at the International Symposium on UDC in Relation to Other Indexing Languages (Herceg Novi) (1971) are mentioned. The questions posed to UDC are enumerated. The emergence of these questions is viewed in the historical perspective of providing access to information on a global scale and of the development of UDC. The need for basing the design and development of UDC on a sound dynamic general theory of library classification is emphasised. It is shown that the almost impossible task of enumerating and arranging a very large number of subjects almost tending to infinity in a helpful sequence is reduced by the general theory of library classification developed in India to the enumeration and arrangement of a small number of (1) Main Subjects; (2) Basic Subjects going with one or the other of the Main Subjects; and (3) Isolates in each array in the schedule of isolates, the arrangement in a helpful sequence in these cases being determinable by H few objective principles instead of by flair.